Uso do software Geogebra no ensino e aprendizagem de funções afins e quadráticas - Flores, Teblas (2018)
This text was elaborated with the intention of assisting Mathematics teachers who work in Basic Education in the teaching and learning process of linear and quadratic functions through new practices with Geogebra dynamic Mathematics software. In the text, are been suggested a constructive approach through a set of reflections and discussions of a didactic and practical nature directed to the classroom, a group that gradually evolves towards the elaboration of formal concepts and properties, without departing from its practical and everyday character.